Systematic Analysis of the Impact of R-Methylation on RBPs-RNA Interactions: A Proteomic Approach - Maniaci, Marianna; Boffo, Francesca Ludovica; Massignani, Enrico; Bonaldi, Tiziana (Frontiers in Molecular Biosciences, 2021)
RNA binding proteins (RBPs) bind RNAs through specific RNA-binding domains, generating multi-molecular complexes known as ribonucleoproteins (RNPs). Various post-translational modifications (PTMs) have been described to regulate RBP structure, subcellular localization, and interactions with other proteins or RNAs. Recent proteome-wide experiments showed that RBPs are the most representative group within the class of arginine (R)-methylated proteins. Moreover, emerging evidence suggests that this modification plays a role in the regulation of RBP-RNA interaction. Nevertheless, a systematic analysis of how changes in protein-R-methylation can affect globally RBPs-RNA interactions is still missing. We describe here a quantitative proteomics approach to profile global changes of RBP-RNA interactions upon the modulation of type I and II protein arginine methyltransferases (PRMT). By coupling the recently described Orthogonal Organic Phase Separation (OOPS) strategy with SILAC labelling and pharmacological modulation of PRMTs, we profile RNA-protein interaction dynamics in dependence of protein-R-methylation. Data are available via ProteomeXchange with identifier PXD024601.